2.8 dB conversion gain broadband HBT–HEMT balanced frequency tripler with high harmonic suppression. Issue 11 (1st May 2014) - Chen, Guan‐Yu; Chang, Hong‐Yeh; Weng, Shou‐Hsien; Hsin, Yue‐Ming; Wang, Yu‐Chi
Abstract : A 10.2–12.6 GHz balanced heterojunction bipolar transistor (HBT)–high electron mobility transistor (HEMT) frequency tripler is presented. A pair of common‐base/common‐emitter HBTs is used to generate in‐phase and out‐of‐phase harmonics. Two bandpass filters are utilised as matching networks to enhance the harmonic suppression. A common‐gate/common‐source HEMT active balun is employed to combine the third harmonic in‐phase and provide conversion gain. The proposed frequency tripler shows a conversion gain of 2.8 dB, a fractional bandwidth of 21.2% and a fundamental suppression higher than 47 dB.